2006
DOI: 10.1155/jnm/2006/32803
|View full text |Cite
|
Sign up to set email alerts
|

Damping Augmentation of Nanocomposites Using Carbon Nanofiber Paper

Abstract: Vacuum-assisted resin transfer molding (VARTM) process was used to fabricate the nanocomposites through integrating carbon nanofiber paper into traditional glass fiber reinforced composites. The carbon nanofiber paper had a porous structure with highly entangled carbon nanofibers and short glass fibers. In this study, the carbon nanofiber paper was employed as an interlayer and surface layer of composite laminates to enhance the damping properties. Experiments conducted using the nanocomposite beam indicated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 24 publications
2
35
0
Order By: Relevance
“…The possible reason of the marginal increase when the content of clay nanofibers is more than 3% might be that the formation of clusters of nanofibers. Others authors as [29,30] also observed a very slight change in the natural frequencies due to inclusion of nanofibers. In general the change in the stiffness of the nano-enriched composite depends on nano-inclusion and its properties.…”
Section: Effect Of Nanofibers On the Natural Frequenciesmentioning
confidence: 85%
See 1 more Smart Citation
“…The possible reason of the marginal increase when the content of clay nanofibers is more than 3% might be that the formation of clusters of nanofibers. Others authors as [29,30] also observed a very slight change in the natural frequencies due to inclusion of nanofibers. In general the change in the stiffness of the nano-enriched composite depends on nano-inclusion and its properties.…”
Section: Effect Of Nanofibers On the Natural Frequenciesmentioning
confidence: 85%
“…This work found that damping ratio of carbon fibre composite panels reinforced with nylon nanofibers is about 62% higher than the damping of virgin panels. Another study conducted by Jihua Gou et al [29] indicated that the damping ratio of composite laminates enriched with carbon nanotubes was up to 200% higher as compared to the damping in virgin composites. Naser Kordani et al [30] also concluded that the damping ratio can increase considerably due the inclusion of nanofibers.…”
Section: Effect Of Nanofibers On the Damping Ratiomentioning
confidence: 99%
“…Electrically actuating SMPs by electrical resistive heating has been intensively studied. By mixing carbon black and chopped short carbon fiber into styrene-based SMP, Lu et al [17] successfully actuated the SMPs by electrical resistivity heat. Carbon nanofibers (CNFs) have also been used as conductive filler for the actuation of SMPs [18].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, those traditional fabrication methods cannot achieve high-level nanoparticles loading, which is critical for enhancing the conductivity of SMP nanocomposites. Recently, a unique technique of pre-forming conductive CNFs as a sheet or paper has been explored for multifunctional material applications [16,17]. High-quality self-assembled CNFP is made by infiltrating the suspension of CNFs through a hydrophilic or hydrophobic membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Nano particles make a better inter phase property which affect the damping characteristics of composites [18]. Jiua et al [9] conducted experiments on nano composite beams and showed 200-700% increase in damping ratios at higher frequencies. Antonio et al [2] worked on low velocity impact response of fiber glass-epoxy-laminate with 1%, to 10% organically modified MMT ceramic nanoclay and observed some variation in natural frequencies and also observed that 5% clay addition is optimum for improvement in damping.…”
Section: Introductionmentioning
confidence: 99%